(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
Bank NTT is the sole financial institution operating within the NTT region, hence holding a monopoly over the regional banking sector. The application of GCG (Good Corporate Governance) is necessary to enhance banks’ performance. Hence, the primary objective of this study is to examine the execution of effective corporate governance practices inside Bank NTT. This study aims to examine the fundamental tenets of effective corporate governance, encompassing transparency, accountability, responsibility, independence, and fairness. The research methodology employed in this study involves using documents, specifically secondary data sourced from the Bank NTT website. This dataset is anticipated to enable scholars to conduct an analysis of the five principles. The findings indicate that Bank NTT has successfully applied the principles of Good Corporate Governance (GCG). This is supported by the acquisition of the prestigious title of Top Bank in KBMI 1 Category 2022.